Impact of Thrombophilia on Risk of Arterial Ischemic Stroke or Cerebral Sinovenous Thrombosis in Neonates and Children: A Systematic Review and Meta-Analysis of Observational Studies - Kenet, Gili; Lütkhoff, Lisa K.; Albisetti, Manuela; Bernard, Timothy; Bonduel, Mariana; Brandao, Leonardo; Chabrier, Stephane; Chan, Anthony; deVeber, Gabrielle; Fiedler, Barbara; Fullerton, Heather J.; Goldenberg, Neil A.; et al. (Circulation (New York, N.Y.), 2010)
Background— The aim of this study was to estimate the impact of thrombophilia on risk of first childhood stroke through a meta-analysis of published observational studies. Methods and Results— A systematic search of electronic databases (Medline via PubMed, EMBASE, OVID, Web of Science, The Cochrane Library) for studies published from 1970 to 2009 was conducted. Data on year of publication, study design, country of origin, number of patients/control subjects, ethnicity, stroke type (arterial ischemic stroke [AIS], cerebral venous sinus thrombosis [CSVT]) were abstracted. Publication bias indicator and heterogeneity across studies were evaluated, and summary odds ratios (ORs) and 95% confidence intervals (CIs) were calculated with fixed-effects or random-effects models. Twenty-two of 185 references met inclusion criteria. Thus, 1764 patients (arterial ischemic stroke [AIS], 1526; cerebral sinus venous thrombosis [CSVT], 238) and 2799 control subjects (neonate to 18 years of age) were enrolled. No significant heterogeneity was discerned across studies, and no publication bias was detected. A statistically significant association with first stroke was demonstrated for each thrombophilia trait evaluated, with no difference found between AIS and CSVT. Summary ORs (fixed-effects model) were as follows: antithrombin deficiency, 7.06 (95% CI, 2.44 to 22.42); protein C deficiency, 8.76 (95% CI, 4.53 to 16.96); protein S deficiency, 3.20 (95% CI, 1.22 to 8.40), factor V G1691A, 3.26 (95% CI, 2.59 to 4.10); factor II G20210A, 2.43 (95% CI, 1.67 to 3.51); MTHFR C677T (AIS), 1.58 (95% CI, 1.20 to 2.08); antiphospholipid antibodies (AIS), 6.95 (95% CI, 3.67 to 13.14); elevated lipoprotein(a), 6.27 (95% CI, 4.52 to 8.69), and combined thrombophilias, 11.86 (95% CI, 5.93 to 23.73). In the 6 exclusively perinatal AIS studies, summary ORs were as follows: factor V, 3.56 (95% CI, 2.29 to 5.53); and factor II, 2.02 (95% CI, 1.02 to 3.99). Conclusions— The present meta-analysis indicates that thrombophilias serve as risk factors for incident stroke. However, the impact of thrombophilias on outcome and recurrence risk needs to be further investigated.